Effect of Water Retaining Polymer Application on the Productivity of Chickpea (Cicer arietinum) Under Dryland Agriculture - Dingre, S. K.; Pawar, D. D.; Shinde, M. G.; Tarte, G. L. (International Journal of Bio-resource and Stress Management, 2017)
A field experiment conducted during 2009−10 and 2010−11 to assess the effect of water retaining polymer on chickpea in light soils of western Maharashtra. The experiment comprised of 7.5, 10.0, 12.5, 15.0 17.5 and 20 kg ha-1 application of water retaining polymer before sowing and results were compared with conventional method in randomized block design with three replications. The superior chickpea yield (22.5 q ha-1) obtained when water retaining polymer applied @ 15 kg ha-1 which was significantly on par with 12.5 kg ha-1 application (21.2 q ha-1). The conventional method of chickpea cultivation recorded significantly lowest yield (14.1 q ha-1). Pooled data indicated that water retaining polymer application increase the yield by 8 to 55%. The 20 kg ha-1 water retaining polymerused less quantity of water (21.43 cm) over conventional method (27.35 cm) with 10.3 to 27.6% water saving. Field water use efficiency improved considerably under application of 15 kg ha-1 water retaining polymer (10.1 kg ha-1 mm-1) among all treatments studied. The higher gross monetary returns (Rs. 67500 ha-1), net monetary returns (` 28757 ha-1) and B: C ratio (1.7) were also obtained with 15 kg ha-1 polymer application, however it was on par with the economical parameters obtained under 12.5 kg ha-1 polymer applied. Hence, 12.5 kg ha-1 water retaining polymer application before sowing was found suitable for chickpea cultivation in dry land areas of western India.